2014
DOI: 10.1111/ecc.12223
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for patients with cancer: psychological flexibility and the potential utility of Acceptance and Commitment Therapy

Abstract: Cancer is an illness affecting patients' physical and psychosocial wellbeing: high numbers report problematic levels of distress at many points through diagnosis, treatment and survivorship. Conclusive evidence for the long-term benefits of psychological interventions is lacking and this may be because (a) they employ a too

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 95 publications
8
159
1
3
Order By: Relevance
“…He views the experience of distress as an intrinsic part of the process of realignment of implicit internal schemas (of self, others, body, future, etc) that cancer has rudely disrupted. Nick Hulbert‐Williams and others are proposing cross‐diagnostic interventions for cancer distress, based on contextual science and the ideas of Steven Hayes' relational frame theory . Here, resolving the distress associated with cancer (or, for the matter, any health threat) is seen as a process of developing psychological flexibility, acceptance, and self‐compassion for the full range of human reactions, rather than avoiding and suppressing.…”
Section: An Alternative Vision—like Personalised Medicine Personalismentioning
confidence: 99%
“…He views the experience of distress as an intrinsic part of the process of realignment of implicit internal schemas (of self, others, body, future, etc) that cancer has rudely disrupted. Nick Hulbert‐Williams and others are proposing cross‐diagnostic interventions for cancer distress, based on contextual science and the ideas of Steven Hayes' relational frame theory . Here, resolving the distress associated with cancer (or, for the matter, any health threat) is seen as a process of developing psychological flexibility, acceptance, and self‐compassion for the full range of human reactions, rather than avoiding and suppressing.…”
Section: An Alternative Vision—like Personalised Medicine Personalismentioning
confidence: 99%
“…Furthermore, the incidence of patient‘s psychosocial needs may vary at different stages of the cancer pathway (Gil, Costa, Hilker, & Benito, ; King et al., ). Although a subset of patients are at high risk of depression, symptomatic distress and subclinical mood disturbances are more prevalent (Hulbert‐Williams, Storey, & Wilson, ). Additionally, a significant minority of patients adjust and cope well, such that following successful treatment they are not dissimilar to the general population in terms of their psychological well‐being (Mitchell et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Coyne & van Sonderen, 2012). A recent literature review by Hulbert-Williams, Storey & Wilson (2015) suggested that the inconsistency in effectiveness of interventions for cancer-related distress may be due to a reliance on problem-focussed intervention frameworks, and that third-wave approaches such as Acceptance and Commitment Therapy (ACT) may hold potential. In cancer samples specifically, interventions that utilise ACT-based techniques have been shown to feasible for delivery in community care settings (Arch & Mitchell, 2015) and of benefit in improving mood and quality of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Rost et al, 2012;Feros et al, 2013). However, this literature is small and in many cases methodologically poor, and there is a need for further, more robustly designed empirical research (Hulbert-Williams, Storey, & Wilson, 2015).…”
Section: Introductionmentioning
confidence: 99%